Pemberdayaan Masyarakat Dengan Penanaman Tumbuhan Di Sekitar Lingkungan Masyarakat Di Desa Tangkahan Durian Kecamatan Brandan Barat - Alfian Tanjung; Fenny Mustika Piliang (Yayasan Rahmat Islamiyah, 2023)
Global warming that is happening at this time can increase the temperature of the earth's surface which is a problem faced by almost all countries in the world. Rising earth's surface temperature or ground surface temperature is always a problem. On average, big cities in Indonesia have experienced the negative effects of global warming every day. The impact was no exception in Tangkahan Durian Village, Brandan Barat District. So it is very important to re-organize socialization related to the importance of planting and caring for trees in the environment where we live in the community, especially in the yard of the house, especially rural communities. The results of this counseling have resulted in increased knowledge of the village community and village officials about the importance of planting and caring for trees in homes, especially in the environment where we live, especially those who have large yards.